The future skill-sets expectations of IT graduates in Malaysia IT outsourcing industry - Ahlan, Abdul Rahman; Arshad, Yusri; Suhaimi, Mohd Adam; Hussin, Husnayati (WSEAS Press, 2008)
The issue of IT outsourcing (ITO) impact on IT workforce has been at the forefront agenda of many discussions in many developed countries so much so that the concerns have been tense in that more IT jobs will be transferred to developing countries which provide IT outsourcing services. In addition, with the growth of IT outsourcing and emerging new outsourcing business models such as utility demand, application service provider, business process outsourcing, offshore outsourcing and many more servicing different industry vertical sectors increase the demand for multiple IT skills and capabilities of IT workforce. In this study, we review relevant literature, newspapers and non-academic articles, websites of companies, governments and non-governmental organisations and others. An outsourcing Malaysia (OM) CEO roundtable discussion was also held to hear the practitioners' views on the topic. Further to that, we sought in-depth insights from seven senior executive managements in service provider firms on the skill sets requirements of fresh IT graduates to fulfill the market needs of IT outsourcing in Malaysia. The four-member research team found that technical, soft and problem-solving skills are the main concerns raised by the key informants. This is in line with the literature review and also the present higher education policy concerns by the Malaysia government.